Exploring the Proteomic Alterations from Untreated and Cryoablation and Irradiation Treated Giant Cell Tumors of Bone Using Liquid-Chromatography Tandem Mass Spectrometry - Rashmi Madda; Chao-Ming Chen; Cheng-Fong Chen; Jir-You Wang; Po-Kuei Wu; Wei-Ming Chen (Molecules, 2020)
Giant cell tumors of bone (GCT) are benign tumors that show a locally aggressive nature and affect bones’ architecture. Recently, cryoablation and irradiation treatments have shown promising results in GCT patients with faster recovery and less recurrence and metastasis. Therefore, it became a gold standard surgical treatment for patients. Hence, we have compared GCT-untreated, cryoablation, and irradiation-treated samples to identify protein alterations using high-frequency liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS/MS). Our label-free quantification analysis revealed a total of 107 proteins (p < 0.01) with 26 up-regulated (< 2-folds to 5-fold), and 81 down-regulated (> 0.1 to 0.5 folds) proteins were identified from GCT-untreated and treated groups. Based on pathway analysis, most of the identified up-regulated proteins involved in critical metabolic functions associated with tumor proliferation, angiogenesis, and metastasis. On the other hand, the down-regulated proteins involved in glycolysis, tumor microenvironment, and apoptosis. The observed higher expressions of matrix metalloproteinase 9 (MMP9) and TGF-beta in the GCT-untreated group associated with bones’ osteolytic process. Interestingly, both the proteins showed reduced expressions after cryoablation treatment, and contrast expressions identified in the irradiation treated group. Therefore, these expressions were confirmed by immunoblot analysis. In addition to these, several glycolytic enzymes, immune markers, extracellular matrix (ECM), and heat shock proteins showed adverse expressions in the GCT-untreated group were identified with favorable regulations after treatment. Therefore, the identified expression profiles will provide a better picture of treatment efficacy and effect on the molecular environment of GCT.